The effects of teleworking on mental health in the context of the COVID-19 pandemic (Research, Society and Development, 2023)
This article aims to analyze in the light of the concepts developed by Michel Foucault the effects produced in the mental health of servers of a Court of Justice in the Northeast Region of Brazil that worked in the modality of Telework in the context of the pandemic of COVID-19. This is a qualitative study, with cartographic guidelines, conducted through individual narrative interviews and analyzed from the theoretical contribution of Foucauldian arch-genealogy. The results showed that the participants' narratives evidenced that telework arising from the COVID-19 pandemic revealed marks of the biopolitics in force by stimulating in the individual the management over his life and the responsibility for his physical and mental health. The pressures experienced through productivity and vigilance were recurrent, revealing the effects produced in an emotional disorientation such as the feeling of loneliness, mental exhaustion, panic, anxiety, and depression. The effects were not only felt in a negative way, all of them produced knowledge from these power relations facing the mechanisms of governmentality, with attitudes of resignification and transformation in their narratives. Positive attitudes in the care-of-self were used, such as: setting limits, managing personal, family, and professional time, as well as taking care of physical and mental health.